2007
DOI: 10.1152/ajpcell.00001.2007
|View full text |Cite
|
Sign up to set email alerts
|

Roles of wound geometry, wound size, and extracellular matrix in the healing response of bovine corneal endothelial cells in culture

Abstract: It has classically been accepted that the healing of narrow wounds in epithelia occurs by the formation of a contractile actin cable, while wide wounds are resurfaced by lamellipodia-dependent migration of border cells into the denuded area. To further investigate the general validity of this idea, we performed systematic experiments of the roles of wound geometry, wound size, and extracellular matrix (ECM) in wound healing in monolayers of bovine corneal endothelial cells, a system shown here to predominantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 50 publications
5
25
0
Order By: Relevance
“…Our present study also demonstrates that in situ it co-localizes around the cell periphery with N-cadherin. Previous studies of confluent cultures of bovine endothelial cells have shown that N-cadherin localization is also confined to the cell periphery (Chifflet et al 2004;Chen et al 2007;Grasso et al 2007). During normal wound repair, ZO-1 redistributes as speckled focal points in cells entering the injury area.…”
Section: Discussionmentioning
confidence: 97%
“…Our present study also demonstrates that in situ it co-localizes around the cell periphery with N-cadherin. Previous studies of confluent cultures of bovine endothelial cells have shown that N-cadherin localization is also confined to the cell periphery (Chifflet et al 2004;Chen et al 2007;Grasso et al 2007). During normal wound repair, ZO-1 redistributes as speckled focal points in cells entering the injury area.…”
Section: Discussionmentioning
confidence: 97%
“…When cells reached ,80% confluence, a scratch was generated on the confluent monolayer using a silicon-coated pipette tip, which preserved the extracellular matrix across the scratched area (Grasso et al, 2007). Photographs showing the areas of the wounds in the control group and test group were taken at specific time-points up to 24 h. The wound areas were quantified by using cell migration analysis software (Muscale LLC., Scottsdale, AZ).…”
Section: Wound-healing Assaymentioning
confidence: 99%
“…Thus, Brock et al [9] demonstrated that when the formation of the actin cable is disrupted in embryo chick wounds, cells develop lamellipodia and the healing process may be compromised. Alternatively, Grasso et al [16] showed that the actin cable is not formed when the extracellular matrix is preserved after wounding in in vitro cultures of corneal endothelial cells, and lamellipodiainduced migration was obtained independently of wound shape or size. The migration mechanism may as well be influenced by the size of the wound-significantly smaller in embryos [9,26]-and growth factor levels-much lower in embryonic wounds [36], which allows for a stronger influence of mechanical constrains.…”
Section: Introductionmentioning
confidence: 99%